A execução coletiva pecuniária: uma análise da (não) reparação do dano coletivo no Direito brasileiro - Edilson Vitorelli Diniz Lima (2011)
The research has the main objective of analyze the process used to enforce judicial decisions concerning collective matters in Brazil. Despite the existence of many works at the Field of collective process, the execution has not yet received the same attention, although it is the moment to give to its owner the right that was originally denied. The text presupposes that the main specific problem of enforcing a collective decision is related to obligations of giving money, because the techniques to enforce obligations of doing, not doing and giving are the almost the same in individual and collective process. The work starts with a general contextualization of collective rights, in order to analyze the executive titles that might contain obligations about these rights. Specifically about the agreement of conduct adjustment, it is demonstrated that its nature is of a real transaction. After discussing the possibility of reviewing past collective decisions, which does not contribute, in long terms, for social peace, the research studies the peculiarities of the liquidation process, which is aimed to determine the exact value of the obligation. It is demonstrated, in addition, that the result of this process can perfectly be zero. About the enforcement process, the work defends that it is possible for the judge to charge the defendant of the procedures that are needed for paying the condemnation to each person that suffered the damage. It is also possible to start the enforcement process before the final decision of the original process. If the result suffers alteration, the State, not the author, is going to be obligated for the damages. It is possible, likewise, to repair collective damages by getting properties of the defendant, if they can be used by people. After that, the paper proceeds a qualitative analyses of the use of the fluid recovery in Brazil, to conclude that it cannot be considerate an authentic fluid recovery, because the money is rarely destined to the victim`s class. The compensation of the victims is also aggrieved by the government, who has special laws that allows it to not pay his own debts. In the end, the dissertation concludes that there are many difficulties, both theoretical end practical, to enforce decisions in favor of collective rights. Although Brazilian law can be considered good to recognize collective rights, it is not able to effectively guarantee the compensation to the victims.